Detection of novel coltivirus-related sequences in Haemaphysalis megaspinosa ticks collected from Kanagawa Prefecture, Japan - MATSUMURA, Ryo; KOBAYASHI, Daisuke; ITOYAMA, Kyo; ISAWA, Haruhiko (Journal of Veterinary Medical Science, 2024)
Coltiviruses, belonging to the genus Coltivirus within the family Spinareoviridae, are predominantly tick-borne viruses. Some of these species have been implicated in human diseases; however, their diversity, geographical distribution, and evolutionary dynamics remain inadequately. Therefore, this study was undertaken to explore the phylogenetic evolution of coltiviruses and related viruses. Our results revealed the detection of novel coltivirus-related sequences in adult female Haemaphysalis megaspinosa ticks collected from Kanagawa Prefecture, Japan. Molecular phylogenetic analysis revealed a close association between the sequences and the genome sequences of known coltivirus-related viruses, namely Qinghe tick reovirus and Fennes virus. The putative coltivirus-related virus was tentatively designated the Nakatsu tick virus. This study provides insights into the phylogenetic evolution of coltiviruses and related viruses.